2003
DOI: 10.1124/jpet.103.060236
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-Mediated Up-Regulation of the Mannose Receptor Improves the Delivery of Recombinant Glucocerebrosidase to Gaucher Macrophages

Abstract: Enzyme replacement therapy for Gaucher disease uses a recombinant glucocerebrosidase (Cerezyme) whose oligosaccharide chains have been remodeled to expose the core mannose residues. This modification promotes the uptake of the hydrolase by Gaucher-affected macrophages via mannose receptor-mediated endocytosis. However, studies revealed that amounts of the infused enzyme were also delivered to other mannose receptor-bearing cells such as the liver sinusoidal endothelial cells. To maximize the delivery of Cerezy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…Previous studies have shown that agents and cytokines such as dexamethasone, IL-4 and GM-CSF that promote a mature “deactivated” macrophage phenotype result in the induction of MR expression and altered MR. For example, Cowan et al reported that treatment with dexamethasone increased MR expression on rodent macrophages by as much as 2.5 fold in a time and dose-dependent fashion [69]. Chakraborty et al reported that dexamethasone-induced increases in the MR resulted in increased uptake of Leishmania parasites [29], and Zhu et al demonstrated that dexamethasone treatment increased clearance of glucocerebrocidase by the MR [78]. In data not presented, we examined the effect of positive regulators (dexamethasone, GM-CSF, and IL-4) on MR expression in 43 MR cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that agents and cytokines such as dexamethasone, IL-4 and GM-CSF that promote a mature “deactivated” macrophage phenotype result in the induction of MR expression and altered MR. For example, Cowan et al reported that treatment with dexamethasone increased MR expression on rodent macrophages by as much as 2.5 fold in a time and dose-dependent fashion [69]. Chakraborty et al reported that dexamethasone-induced increases in the MR resulted in increased uptake of Leishmania parasites [29], and Zhu et al demonstrated that dexamethasone treatment increased clearance of glucocerebrocidase by the MR [78]. In data not presented, we examined the effect of positive regulators (dexamethasone, GM-CSF, and IL-4) on MR expression in 43 MR cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were then washed twice with ice cold PBS enriched with Mannan (1 mg/ml). This step is used to inhibit the uptake of the enzyme molecules through the MR [17]. To further ensure release of any proteins bound non-specifically to the membrane half of the cells were washed with ice cold glycine buffer: (0.8% NaCl, 0.038% KCl, 0.01% MgCl2, 0.01% CaCl2, 0.7% glycine [pH 3]) [18] followed by two additional cold PBS washes.…”
Section: Methodsmentioning
confidence: 99%
“…The procedures used to assay enzyme uptake into the rat alveolar macrophage cells (NR8383) were the same as those reported previously except that rhGAA was used in lieu of Cerezyme [29]. Cells were lysed in GAA assay buffer (0.2 M sodium acetate and 0.4 M potassium chloride, pH 4.3) containing 0.1 % Triton X-100.…”
Section: Binding and Cell-uptake Studiesmentioning
confidence: 99%